2010
DOI: 10.1093/brain/awq034
|View full text |Cite
|
Sign up to set email alerts
|

Rescuing vasculature with intravenous angiopoietin-1 and  v 3 integrin peptide is protective after spinal cord injury

Abstract: Blood vessel loss and inflammation cause secondary degeneration following spinal cord injury. Angiopoietin-1 through the Tie2 receptor, and other ligands through alphavbeta3 integrin, promote endothelial cell survival during developmental or tumour angiogenesis. Here, daily intravenous injections with an alphavbeta3-binding peptide named C16 or an angiopoietin-1 mimetic following a spinal cord contusion at thoracic level 9 in mice rescued epicentre blood vessels, white matter and locomotor function, and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
148
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(166 citation statements)
references
References 78 publications
16
148
2
Order By: Relevance
“…A study by Zhang and colleagues indicated that virallydelivered Ang-1 given days before ischemic brain injury resulted in reduced vascular leakage and decreased lesion volume (Zhang et al, 2002a). Consistent with a recent article on the therapeutic potential of Ang-1 (Han et al, 2010), our results indicate similar improvements of reduced lesion volume and enhanced functional recovery with Ang-1 treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A study by Zhang and colleagues indicated that virallydelivered Ang-1 given days before ischemic brain injury resulted in reduced vascular leakage and decreased lesion volume (Zhang et al, 2002a). Consistent with a recent article on the therapeutic potential of Ang-1 (Han et al, 2010), our results indicate similar improvements of reduced lesion volume and enhanced functional recovery with Ang-1 treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Thurston and associates showed that systemic Ang-1 production by adenoviral gene delivery resulted in reduced vascular leakage induced by VEGF (Thurston et al, 2000), or inflammatory agents (Thurston et al, 1999). A recent study by Han and colleagues indicated that intravenous delivery of Ang-1 had protective effects after SCI (Han et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few studies in the rodent spinal cord injury field have gone beyond 6 weeks post-injury. We (Han et al, 2010), like others (e.g., Kigerl et al, 2006;Rosenberg et al, 2005,), find inflammatory markers such as CD45 for total leukocytes and CD68 for activated microglia still present at 6 weeks post-injury in rats and mice. In humans, activated microglia/macrophages, as detectable by CD68 immunostaining, are also present for weeks to months following spinal cord injury (Fleming et al, 2006).…”
supporting
confidence: 85%
“…Studies in animal models of SCI show that microvascular damage and hypoperfusion is associated with increased degeneration after SCI. 8,11,23 Advanced studies with accurate monitoring via surgically implanted ISP monitors in concordance with neurological improvement scores could contribute to a better understanding of optimal MAP goals in ATCCS patients and provide clear protocols on the issue.…”
Section: Discussionmentioning
confidence: 99%